Histoenzymic Localization of Phosphatases and Oxidoreductases in Buffalo Skin - Debbarma, Debajit (Indian Journal of Veterinary Anatomy, 2018)
The present study was conducted on skin of eight buffaloes collected from the abattoir and Postmortem Hall. The cryostat sections of 10 μm thickness of fresh unfixed tissues were cut at -23oC and incubated in different substrates forhistoenzymic localization of phosphatases and oxidoreductases. The study revealed a variable activity of AKPase, G-6-Pase, SDH, LDH, NADH diaphorase, NADPH diaphorase and G-6-PD in different parts of epidermis and dermis. The enzymicactivity was maximum in stratum basale, sebaceous glands and sweat glands that can be correlated with keratinization of epithelium, formation of glandular secretions in sweat glands and continual differentiation of the cells of sebaceous glands.